EDUKASI TEKNIK BREATHING EXERCISE UNTUK MENGATASI HIPERTENSI PADA LANSIA - Pristianto, Arif; Atingsih, Longgar; Faradilla, Arvindha; Khoirunnisa, Asty; Kartika, Griska Mutiara (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
With a very high prevalence rate in the elderly, hypertension is a sort of non-communicable disease that is chronic, lifelong, and a silent killer. Age, gender, race, obesity, behaviors, and smoking habits are all genetic factors that have an impact on hypertension. The cornerstones of conventional treatment and lifestyle adjustments, including as modifying one's diet, controlling stress, regulating one's exercise levels, abstaining from alcohol, and smoking, support the management of hypertension.. This activity was carried out as a community service at the Ngudi Sehat Posyandu 4 Sanggir Selatan, Colomadu as a process of community service activities that will be carried out in the form of education through outreach activities regarding materials about hypertension and the program of giving Breathing Exercises first and then doing the practice of the counseling. It is hoped that this community service will provide education through counseling about hypertension and provide programs in the form of Breathing Exercises to the community.